THE PRINCIPLE OF EDUCATIONAL STRATEGY IN TEACHING ENGLISH AND ITS ADVANTAGES - Guncha Mamajanova (American Journals, 2023)
In our society today, the teaching of foreign languages, especially English, is developing day by day. The mechanism of teaching methods plays an important role in the process of teaching English. The use of effective method competencies in the classroom is valued as a product of the intellectual approach and research of each faculty member to their profession. The functional serenity of modern pedtechnologies improves the process of integrated communication in the process of language teaching.
Keywords: modern ped-technologies, functional process, intellectual aspect, professional efficiency, methods, ways, approaches